A Quantitative Method for Intraoperative Evaluation of Distal Fibular Malrotation - Huang, Hui; Li, Zihua; Xiao, Fajiao; Xia, Jiang; Li, Bing; Yu, Tao; Zhao, Youguang; Zhou, Haichao; He, Wenbao; Li, Zhendong; Yang, Yunfeng (Frontiers in Surgery, 2022)
Background Due to the low sensitivity of commonly used radiographic parameters for the evaluation of rotational malreduction of the distal fibula under intraoperative fluoroscopy, a quantitative method is needed to make up for this defect. Methods A total of 96 sets of computed tomography images of normal ankles were imported into MIMICS to reconstruct 3D models. The fibula models were rotated along the longitudinal axis from 30 degrees of external rotation to 30 degrees of internal rotation. Virtual X-ray function in MIMICS was used to obtain radiographic images in mortise view. A line was drawn through the tip of the medial malleolus and parallel to the distal tibial plafond, the distances from the medial edge of the fibula to the lateral malleolar fossa cortex and from the medial edge of the fibula to the lateral edge of the fibula were measured on this line, and the ratio of them was calculated and marked as ratio α. Results The mean ratio α for normal ankles was 0.49 ± 0.06, while the 95% confidence interval was 0.48–0.50. The ratio α decreased when the fibula was externally rotated and increased when the fibula was internally rotated. The effects of different genders or different types on each group of data were compared, and the p values were all greater than 0.05. Conclusions This is a new method to quantitatively evaluate rotational malreduction of the distal fibula during operation. The ratio α can correspond to the rotation angle of the fibula. The larger the ratio α, the more the internal rotation of the fibula. Contrarily, the smaller the ratio α, the more the external rotation of the fibula. Making the ratio α close to 0.5 may be an intuitive approach that can be used intraoperatively.